KwaThwaleyakhe Shelter: the faunal remains from a Holocene site in the Thukela Basin, Natal - Plug, I. (Southern African Humanities, 2021)
The faunal remains from the late Holocene hunter-gatherer site kwaThwaleyakhe Shelter provide insight into the past faunal population of the Muden area in Natal. Klipspringer appears to have been readily available in the area during the last 4000 years, including the recent past, although historical records of the presence of the species are vague. The presence of divining objects indicates some form of cultural assimilation from Iron Age communities. The virtual absence of domestic stock suggests that the economic subsistence method was not influenced greatly by contact with Iron Age agropastoralists. To cite this paper: Plug, I. 1993. KwaThwaleyakhe Shelter: the faunal remains from a Holocene site in the Thukela Basin, Natal. Natal Museum Journal of Humanities 5: 37-45.